3D-printed titanium metaphyseal cones in revision total knee arthroplasty with cemented and cementless stems. (1st June 2021) - Anderson, Lucas A.; Christie, Matthew; Blackburn, Brenna E.; Mahan, Chad; Earl, Christian; Pelt, Christopher E.; Peters, Christopher L.; Gililland, Jeremy
Abstract : Aims: Porous metaphyseal cones can be used for fixation in revision total knee arthroplasty (rTKA) and complex TKAs. This metaphyseal fixation has led to some surgeons using shorter cemented stems instead of diaphyseal engaging cementless stems with a potential benefit of ease of obtaining proper alignment without being beholden to the diaphysis. The purpose of this study was to evaluate short term clinical and radiographic outcomes of a series of TKA cases performed using 3D-printed metaphyseal cones. Methods: A retrospective review of 86 rTKAs and nine complex primary TKAs, with an average age of 63.2 years (SD 8.2) and BMI of 34.0 kg/m 2 (SD 8.7), in which metaphyseal cones were used for both femoral and tibial fixation were compared for their knee alignment based on the type of stem used. Overall, 22 knees had cementless stems on both sides, 52 had cemented stems on both sides, and 15 had mixed stems. Postoperative long-standing radiographs were evaluated for coronal and sagittal plane alignment. Adjusted logistic regression models were run to assess malalignment hip-knee-ankle (HKA) alignment beyond ± 3° and sagittal alignment of the tibial and femoral components ± 3° by stem type. Results: No patients had a revision of a cone due to aseptic loosening; however, two had revision surgery due to infection. In all, 26 (27%) patients had HKA malalignment; nine (9.5%) patients had sagittal plane malalignment, five (5.6%) of the tibia, and four (10.8%) of the femur. After adjusting for age, sex, and BMI, there was a significantly increased risk for malalignment when a cone was used and both the femur and tibia had cementless compared to cemented stems (odds ratio 3.19, 95% confidence interval 1.01 to 10.05). Conclusion: Porous 3D-printed cones provide excellent metaphyseal fixation. However, these central cones make the use of offset couplers difficult and may generate malalignment with cementless stems. We found 3.19-times higher odds of malalignment in our TKAs performed with metaphyseal cones and both femoral and tibial cementless stems. Cite this article: Bone Joint J  2021;103-B(6 Supple A):150–157.